Good Night, Little Rainbow Fish - Pfister, Marcus (New York : North-South Books, 2012)
Rainbow Fish's devoted Mommy offers reassurances to him when he cannot fall asleep that she will always protect him from the perils of the sea such as an octopus's ink cloud, a hungry shark, and a jellyfish's sting.
Keywords: Fishes -- Fiction; Mother-child relationship -- Fiction; Sleep -- Fiction; Bedtime -- Fiction